Persepsi Pendengar Terhadap Berita Pendidikan Pada Program Siaran Sore Radio Madama 87.7 Fm - Yulhaidir, Yulhaidir; Annisa, Shinta Hutami (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Perception is the act of compiling, recognizing, and interpreting sensory information in order to provide an overview and understanding of the environment. This research is aimed to determine the listener's perception of educational news on the Madama radio afternoon broadcast program. The data collection used primary data obtained from in-depth interviews with Madama radio listeners who are still students and college students. The results of these interviews had been validated with several theories in this research in the form of expert opinions and the results of previous studies. The results showed that the listener's perception of educational news on the Madama radio afternoon broadcast program was the result of research showing the reality that most listeners liked the educational news on the Madama radio afternoon broadcast program, either from students or college students. With what the researchers have done in the field, listeners' perceptions of educational news on the afternoon broadcast program tend to like the news, although out of the five informants there are still those who think that they rarely listen to the radio.